Quantification of the Electromechanical Measurements by Piezoresponse Force Microscopy. Issue 47 (21st October 2022) - Buragohain, Pratyush; Lu, Haidong; Richter, Claudia; Schenk, Tony; Kariuki, Pamenas; Glinsek, Sebastjan; Funakubo, Hiroshi; Íñiguez, Jorge; Defay, Emmanuel; Schroeder, Uwe; Gruverman, Alexei
Abstract: Piezoresponse force microscopy (PFM) is widely used for characterization and exploration of the nanoscale properties of ferroelectrics. However, quantification of the PFM signal is challenging due to the convolution of various extrinsic and intrinsic contributions. Although quantification of the PFM amplitude signal has received considerable attention, quantification of the PFM phase signal has not been addressed. A properly calibrated PFM phase signal can provide valuable information on the sign of the local piezoelectric coefficient—an important and nontrivial issue for emerging ferroelectrics. In this work, two complementary methodologies to calibrate the PFM phase signal are discussed. The first approach is based on using a standard reference sample with well‐known independently measured piezoelectric coefficients, while the second approach exploits the electrostatic sample–cantilever interactions to determine the parasitic phase offset. Application of these methodologies to studies of the piezoelectric behavior in ferroelectric HfO2 ‐based thin‐film capacitors reveals intriguing variations in the sign of the longitudinal piezoelectric coefficient, d 33, eff . It is shown that the piezoelectric properties of the HfO2 ‐based capacitors are inherently sensitive to their thickness, electrodes, as well as deposition methods, and can exhibit wide variations including a d 33, eff sign change within a single device. Abstract : Coexistence of the regions with positive and negative piezoelectricity within the 20 nm‐thick La:HfO2 capacitor is revealed by piezoresponse force microscopy (PFM) local spectroscopy and imaging. A PFM loop obtained in region L1 exhibits a negative piezoelectric coefficient, while a mirror‐reflected PFM loop is obtained from region L2 with positive piezoelectricity.